Keseimbangan Kehidupan Kerja (Work-Life Balance) dalam Meningkatkan Kinerja Karyawan: Studi Kasus pada PT. Putra Celebes Utama Mandiri - Batara P, Nevia Anggita; Permady Yusuf, Dhea; Sambara’, Kordiana; Rasinan, Djusniati (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research was conducted to determine the work-life balance in improving the performance of employees of PT Putra Celebes Utama Mandiri. The purpose of this study was to determine the purpose of work-life balance at PT. Putra Celebes Utama Mandiri. organize and adjust between life and work balance at PT. Putra Celebes Utama Mandiri. The research method used is a qualitative method with a phenomenological approach. The number of research informants was 3 employee informants. The research location is at PT Putra Celebes Utama Mandiri. In connection with the results of in-depth interviews that the better the work-life balance that employees have, the performance of employees will increase to be able to achieve good quality.